2015
DOI: 10.1249/mss.0000000000000555
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bone Turnover Markers and Cytokines to High-Intensity Low-Impact Exercise

Abstract: These results suggest that HIE stimulates a response in bone turnover markers and cytokines and that a correlation exists between immune and skeletal responses to this form of exercise. This type of exercise may benefit individuals for whom high-impact exercise might be contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 33 publications
6
47
0
Order By: Relevance
“…This type of catabolic-anabolic coupling is in line with previous findings of reduced IGF-1 levels shortly following intense aerobic training in adolescents [21]. It is also parallel to the acute inflammatory response immediately post-exercise [20], followed by a general reduced inflammatory status following training [22]. Thus, the immediate increase in PTH and sclerostin may reflect an initial catabolic response, which is later followed by an anabolic response to exercise.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This type of catabolic-anabolic coupling is in line with previous findings of reduced IGF-1 levels shortly following intense aerobic training in adolescents [21]. It is also parallel to the acute inflammatory response immediately post-exercise [20], followed by a general reduced inflammatory status following training [22]. Thus, the immediate increase in PTH and sclerostin may reflect an initial catabolic response, which is later followed by an anabolic response to exercise.…”
Section: Discussionsupporting
confidence: 86%
“…Of note, one may also speculate that the exercise session resulted in an initial catabolic response, especially in men, to be followed later by an anabolic response. Indeed, immediately following intense exercise, Mezil et al [20] demonstrated elevated bone resorption markers in young men. Twenty-four hours following exercise, we observed an increase in bone-specific alkaline phosphatase, reflecting an increase in bone formation, in both boys and men [12].…”
Section: Discussionmentioning
confidence: 99%
“…We measured insulin levels and found no significant changes. Additionally, it should be noted that the serum used in the present study was assessed for cytokine levels previously [42]. IL-1α, IL-1β, IL-10, IL6, and TNF-α levels were found to be increased 5 min post-exercise and returned to baseline levels 1 h and 24 h post-exercise [42].…”
Section: Discussionmentioning
confidence: 97%
“…Although it is easier to understand the lack of effect for low-level exercise because a threshold of strain is needed, it is hard to understand why a high level of exercise failed to affect either bone formation or bone resorption [56][57][58]. Previous studies have shown that excessive exercise could lead to an increase in bone resorption.…”
Section: Exercise Improved Bone Mass and Strength By Suppressing Bonementioning
confidence: 99%